Bile acids as a key target: traditional Chinese medicine for precision management of insulin resistance in type 2 diabetes mellitus through the gut microbiota-bile acids axis - Wang, Yu; Yu, Jing; Chen, Binqin; Jin, Wenqi; Wang, Meili; Chen, Xuenan; Jian, Mengqiong; Sun, Liwei; Piao, Chunli (Frontiers in Endocrinology, 2024)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease caused by insulin resistance (IR) and insufficient insulin secretion. Its characteristic pathophysiological processes involve the interaction of multiple mechanisms. In recent years, globally, the prevalence of T2DM has shown a sharp rise due to profound changes in socio-economic structure, the persistent influence of environmental factors, and the complex role of genetic background. It is worth noting that most T2DM patients show significant IR, which further exacerbates the difficulty of disease progression and prevention. In the process of extensively exploring the pathogenesis of T2DM, the dynamic equilibrium of gut microbes and its diverse metabolic activities have increasingly emphasized its central role in the pathophysiological process of T2DM. Bile acids (BAs) metabolism, as a crucial link between gut microbes and the development of T2DM, not only precisely regulates lipid absorption and metabolism but also profoundly influences glucose homeostasis and energy balance through intricate signaling pathways, thus playing a pivotal role in IR progression in T2DM. This review aims to delve into the specific mechanism through which BAs contribute to the development of IR in T2DM, especially emphasizing how gut microbes mediate the metabolic transformation of BAs based on current traditional Chinese medicine research. Ultimately, it seeks to offer new insights into the prevention and treatment of T2DM. Diet, genetics, and the environment intricately sculpt the gut microbiota and BAs metabolism, influencing T2DM-IR. The research has illuminated the significant impact of single herbal medicine, TCM formulae, and external therapeutic methods such as electroacupuncture on the BAs pool through perturbations in gut microbiota structure.This interaction affects glucose and lipid metabolism as well as insulin sensitivity.Additionally, multiple pathways including BA-FXR-SHP, BA-FXR-FGFR15/19, BA-FXR-NLRP3, BA-TGR5-GLP-1, BAs-TGR5/FXR signaling pathways have been identified through which the BAs pool significantly alter blood glucose levels and improve IR. These findings offer novel approaches for enhancing IR and managing metabolic disorders among patients with T2DM.